2021
DOI: 10.1021/acs.jpclett.0c03504
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nuclear Magnetic Resonance Investigation of Molecular Adsorption and Kinetics in Metal–Organic Framework UiO-66

Abstract: Thermodynamic and kinetic properties of molecular adsorption and transport in metal–organic frameworks (MOFs) are crucially important for many applications, including gas adsorption, filtration, and remediation of harmful chemicals. Using the in situ 1H nuclear magnetic resonance (NMR) isotherm technique, we measured macroscopic thermodynamic and kinetic properties such as isotherms and rates of mass transfer while simultaneously obtaining microscopic information revealed by adsorbed molecules via NMR. Upon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 36 publications
5
19
0
Order By: Relevance
“…The IPA adsorption isotherms in pristine and defective UiO-66 were conducted via the in situ NMRdetective systems. 31 As shown in Figure 2, the simulation results agree well with the NMR measurements, which further validates the model and the force field parameters utilized in this work. The results in Figure 2 also show that the saturation adsorptions in pristine UiO-66 and UiO-66 with one missing link and two missing links, are respectively 20, 22, and 24 IPA molecules per unit cell and that IPA adsorption increases when there are more linkers removed from the pristine UiO-66.…”
Section: Models and Simulation Detailssupporting
confidence: 80%
See 1 more Smart Citation
“…The IPA adsorption isotherms in pristine and defective UiO-66 were conducted via the in situ NMRdetective systems. 31 As shown in Figure 2, the simulation results agree well with the NMR measurements, which further validates the model and the force field parameters utilized in this work. The results in Figure 2 also show that the saturation adsorptions in pristine UiO-66 and UiO-66 with one missing link and two missing links, are respectively 20, 22, and 24 IPA molecules per unit cell and that IPA adsorption increases when there are more linkers removed from the pristine UiO-66.…”
Section: Models and Simulation Detailssupporting
confidence: 80%
“…A cutoff of 12 Å was applied to all LJ interactions, and the long-range electrostatic interactions were treated by the Ewald summation method. The IPA adsorption isotherms in pristine and defective UiO-66 were conducted via the in situ NMR-detective systems . As shown in Figure , the simulation results agree well with the NMR measurements, which further validates the model and the force field parameters utilized in this work.…”
Section: Models and Simulation Detailssupporting
confidence: 71%
“…Effect of Flexibility on the Adsorption of IPA in UiO-66. An et al studied the uptake of IPA from solid-state NMR and gravimetric adsorption isotherms in UiO-66 at 291 K. 65 They compared simulated isotherms for IPA using rigid models of pristine, 8 and 17% missing linker defect UiO-66 having formate capping groups with the experiments. They found that the saturation loading from simulations of 17% defective MOF was in best agreement with the experiments (Figure S14 in ref 65).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For IPA adsorption isotherms, GCMC simulations were performed at 291 K using snapshots for empty flexible UiO-66, seven IPA molecules/fu, and seven acetone molecules/ fu flexible UiO-66 structures at 298 K. The IPA isotherm was computed at 291 K to match the experiments. 65 The small difference in temperature between the MD snapshots (298 K) and GCMC simulations (291 K) should have a negligible impact on the results. The GCMC simulations on the 10 snapshots for each condition were averaged to obtain an estimation of the isotherm including the effects of framework flexibility, both for empty and for adsorbate-loaded configurations.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Early studies used electromagnets to study NMR relaxation as a function of temperature. Modern day high-field NMR spectroscopy can offer a much more detailed picture, down to the atomic scale, by directly probing the adsorbed phase in terms of structure and dynamics. To date, however, mainly single-point adsorption high-field NMR experiments have been performed, since full isotherm measurements are nontrivial to implement on superconducting NMR instruments, or otherwise deviate from the ideal conditions set as industry standards for isotherm acquisition (e.g., using gravimetric techniques, imaging, etc. ). , Recent studies have attempted to circumvent these limitations with the use of low-field NMR for the study of sorbent materials.…”
Section: Single-pore Mof: Zif-8mentioning
confidence: 99%